Sosialisasi pemanfaatan limbah batang pohon pisang Menjadi bahan additive lumpur dan semen pemboran pada masyarakat Desa Pandau Jaya Kecamatan Siak Hulu Kabupaten Kampar - Muhammad Ariyon; Novia Rita; Idham Khalid; Novrianti Novrianti; Fitrianti Fitrianti (CANANG: Jurnal Pengabdian Masyarakat, 2021)
Some people in Pandau Jaya village have banana trees in their yards, but most people throw away the tree trunks after the fruit is harvested, sometimes the banana stems that have been cut down are only used for fertilizer, animal food or left without further exploiting their potential. For this reason, the Service Team conveyed directly to the community that the waste of the banana stems, if collected, could be used as a useful additive for drilling oil wells, although this is the key to the results of tests conducted at the Petroleum Engineering Laboratory, where the additives are obtained from banana trees. has good quality in covering rock cavities, so as to prevent mud loss during the drilling process. The method used in this community service activity is interactive socialization, discussion and question and answer using supporting facilities and directly to the people of Pandau Jaya Village by providing examples of experimental results that have been carried out at the Petroleum Engineering Laboratory. So that the public can know the process of making additives from banana tree trunks and making drilling mud with the use of these additives. If this research can be applied to the oil field, it can increase income for the community.